PRICING AND SERVICE PERSONNEL (PEOPLE) IN SHAPING PUBLIC INTENTION TO USE HAJJ SAVINGS AT BANK SYARIAH INDONESIA - Andan Sindia Putri; Budi Sukardi (Multazam : Jurnal Manajemen Haji dan Umrah, 2026)
Hajj savings are an important financial instrument for Indonesian Muslims in preparing for the Hajj pilgrimage. This study examines the influence of the 7P marketing mix, namely product, price, place, promotion, people, process, and physical evidence, on public intention to use Hajj savings at Bank Syariah Indonesia (BSI). A quantitative approach was employed using a cross-sectional survey involving 97 respondents from Sembukan Village, Wonogiri Regency and Central Java. Data were analyzed through multiple linear regression after validity, reliability and classical assumption tests. The results indicate that price and people have significant positive effects on public intention to use Hajj savings. Price produced a regression coefficient of 0.279 (p = 0.004), while people produced a coefficient of 0.352 (p = 0.009). Simultaneously, all variables explained 65.5% of the variance (F = 28.229, p <  0.001, Adjusted R² = 0.655). In contrast, product, place, promotion, process and physical evidence showed no significant partial effects. The findings suggest that fair pricing and quality service personnel play important roles in strengthening customer trust and encouraging the adoption of Hajj savings at Bank Syariah Indonesia.